Hypoplastic Left Heart Syndrome: A New Paradigm for an Old Disease? - Grossfeld, Paul (J Cardiovasc Dev Dis, 2019)
Hypoplastic left heart syndrome occurs in up to 3% of all infants born with congenital heart disease and is a leading cause of death in this population. Although there is strong evidence for a genetic component, a specific genetic cause is only known in a small subset of patients, consistent with a multifactorial etiology for the syndrome. There is controversy surrounding the mechanisms underlying the syndrome, which is likely due, in part, to the phenotypic variability of the disease. The most commonly held view is that the “decreased” growth of the left ventricle is due to a decreased flow during a critical period of ventricular development. Research has also been hindered by what has been, up until now, a lack of genetically engineered animal models that faithfully reproduce the human disease. There is a growing body of evidence, nonetheless, indicating that the hypoplasia of the left ventricle is due to a primary defect in ventricular development. In this review, we discuss the evidence demonstrating that, at least for a subset of cases, the chamber hypoplasia is the consequence of hyperplasia of the contained cardiomyocytes. In this regard, hypoplastic left heart syndrome could be viewed as a neonatal form of cardiomyopathy. We also discuss the role of the endocardium in the development of the ventricular hypoplasia, which may provide a mechanistic basis for how impaired flow to the developing ventricle leads to the anatomical changes seen in the syndrome.